Stories of the illness in a changing world of medicine - Modesto Leite, Rolim Neto; Olavo Advincula, Reis Alberto (Perspectivas en Psicología, 2013)
(OBJECTIVES) This study aims at evaluating the impact caused by the doctor's attitude before those patients who would be submitted to a surgical process and their outcome stories expressing their misfortunes and their evaluating the doctor's behavior facing this new situation. (METHODS) The data collection was done through interviews and a questionnaire applied by the psychological team while the patients had their hearts examined. For the process of codification and labeling the CAQDAS (Computer-Assisted Qualitative Data Analysis Software) was used. (RESULTS) Anxiety was almost a unanimous feeling in every story in which the patients had the opportunity to express their feelings arisen by the illness, as well as before a potential surgery. Also, a need of a more human contact with the doctor was told. (CONCLUSION) The patients who had any kind of faith surprisingly had a calmer recovery process. The absence of a more human relation with the doctor gave place to a deeper attachment to a divine figure in an attempt to overcome the fear of death.